Nilai-Nilai Pendidikan Islam Dalam Novel Bulan Terbelah Di Langit Amerika Karya Hanum Salsabiela Rais Dan Rangga Almahendra - SAKINATI, SAHLIA, Dr. Mutohharun Jinan, M.Ag (2017)
Truth of people is vital something determine existence`s in society or in front of God Allah.SWT.. The charity of people include idea/concept, action, and creation. The important element can be basic in consider quality, integrity and scientific someone is exhausted to success creations`s. maybe creation inside literature or another. Novel is divition of literature creation. Novel is one of media to send messages about education, very interesting involve the use of study and teach, such as substance non formal of teach in education world. Because content of novel not only romantic conversation. However now have a lot of Islamic novel such as conten of novel about values of Islamic education. So writer interested to research values of Islamic education of novel Bulan Terbelah di Langit Amerika (BLTA). Purpose of this research is know about values of Islamic education of novel Bulan Terbelah di Langit Amerika. Novel Bulan Terbelah di Langit Amerika constitute of one literature creation the thing which appoint topic about value of Islam education. This novel talk over about western society which decrease accept attendance Islam in this world, especially America after incident bomb in WTC build New York 11 September 2001. In that Novel, writer have a lot of describe about values of Islam education such as position Islam education can not regardless from human life. World without values of Islam education not bright and not better as well as today. This research is a library research and qualitative approach, with primary data of Novel BLTA Hanum Salsabiela Rais and Rangga Almahendra works and secondary data is books, article about Islamic eduation, values of Islam education, and another Hanum book`s. whereas data is a collected by using documentation technique and analyzed by using content analysis. Results of the study show that values of Islam education consist of aqidah education, ibadah education, and akhlak education. Values of aqidah education in this novel about first of faith pillar, faith to God Allah SWT, then fourth of faith pillar, faith to Allah prophets, and the last sixth of faith pillar, faith to qada` and qadar (Allah Fate`s). whereas values of ibadah eduation in this novel about study and read holy Koran. Seen from Azima attitude which teach ibadah to Sarah, Azima teach about read holy Koran. and the last akhlak education in this novel include akhlak wearing certain clothes, akhlak to parent, akhlak of leader, akhlak about good prejudice and akhlak give up prohibition.